Dedolarisasi Global Dan Relevansi Hukum Internasional Terhadap Reformulasi Kebijakan Moneter Indonesia - Juwita, Kiki; Adham S, Sepriyadi; Putri, Ria Wierma; Kasmawati, Rohaini (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
The dominance of the United States Dollar (USD) in the global financial system, a legacy of the Bretton Woods Agreement, is now facing serious challenges due to growing dedollarization efforts by various countries, particularly the BRICS bloc. Geopolitical events, such as the sanctions against Russia in 2022, have accelerated the push to reduce reliance on the USD in order to minimize external economic vulnerabilities and establish a multipolar monetary system. Indonesia, which officially became a member of BRICS in January 2025, views this membership as a strategic move to strengthen global collaboration, advocate for the interests of the Global South, and achieve ambitious domestic economic growth targets. Despite concerns regarding potential threats to its non-aligned foreign policy, Indonesia adopts a pragmatic and gradual hedging strategy, combining engagement with BRICS and Western-led blocs to diversify partnerships and ensure strategic flexibility. This article analyzes the extent to which Indonesia's BRICS membership influences the direction of its national monetary policy from a legal perspective, examining the roles of BRICS initiatives such as the New Development Bank (NDB) and the BRICS Contingent Reserve Arrangement (CRA) in dedollarization efforts, with a particular focus on the use of local currency settlement (LCS) in trade. Furthermore, the article explores the relationship between Indonesia's positive law—particularly the mandate to stabilize the Rupiah under the Bank Indonesia Act and the exceptions to Rupiah usage under the Currency Act—and dedollarization initiatives within the framework of international cooperation. In conclusion, Indonesia's membership in BRICS legally opens up opportunities to diversify its national monetary policy. However, the success of its implementation will heavily depend on Indonesia's ability to navigate complex geopolitical dynamics and manage relationships with various power blocs strategically while maintaining domestic economic stability.